Validation of large eddy simulations for modeling micro-structured enhanced heat transfer surfaces - Li, Puxuan (Kansas State University, 2019)
The focus of this research is to investigate the relationship between the flow characteristics and heat transfer on enhanced surfaces. Internally enhanced surfaces, such as micro-fins, are an important class of heat transfer enhancement in commercial applications. Many research papers discuss the design and optima of these surfaces. However, most previous studies have demonstrated only the macro relationship between the geometries of the micro-fins and heat transfer. The need for a deeper understanding of these fins arose from some currently unsolved problems that limit future development of enhanced surfaces. First, why are increases of heat transfer larger than area increases in micro-finned tubes in most cases? Second, why do internally micro-finned tubes typically have lower heat-transfer-enhanced ratios in laminar and transition flows? First, a comprehensive literature review on internal micro-fins is conducted in this dissertation. Previous experimental and numerical results of internal micro-fins are addressed in the chapter. Second, the dissertation introduces comprehensive experimental measurements including particle image velocimetry (PIV), measurement of the heat transfer coefficient, and accuracy of pressure-drop measurements. Third, validated numerical simulations are then used to predict flow characteristics and heat transfer. Large eddy simulations (LES) are mainly applied to the numerical simulations. The setup of inlet conditions for a LES is a complex and important problem if an accurate numerical result is desired. In this study, PIV results are incorporated into boundary conditions of LES. Parallel processing is an effective computation strategy in which many calculations are carried out simultaneously. In this dissertation, effects of shared-memory parallel processing on LES are presented. The numerical simulations are conducted in the duct with smooth surfaces and enhanced surfaces. The numerical simulation includes both heat conduction in the metal structure and heat convection on the solid-fluid interface. Finally, the dissertation documents how the flow characteristics link with the enhancement of heat transfer in the micro-finned duct, which answers the two problems mentioned in the beginning. The study in the dissertation shows that: (1) a method for generating inflow boundary conditions in a square duct by using PIV measurement results is developed. The new method of generating boundary conditions for LES satisfies the features of good boundary conditions. (2) a new numerical model with LES is used to study the relationship between flow characteristics and heat transfer in a square duct with micro-fins. Good agreements are found when the experimental results are compared to the numerical simulation results.
Keywords: Particle Image Velocimetry (PIV); Large Eddy Simulations (LES); Micro-fins; Heat Transfer Enhancement; Turbulent Structures; Coherent Structures